Prenatal phenobarbital exposure induced evelopmental changes in rat brain and muscle - (:unkn) unknown (My University, 2011)
Female pregnant rats were treated with Phenobarbital which is an antiepileptic drug and is used in the treatment of certain types of seizure and anxiety.Twenty rats were housed in standard cages, with 4 female and 1 male to a cage A commercially prepared diet and clean drinking water were provided adlibitum. Female rats were divided into control and treated groups. The treated groups divided into two subgroups, were given 3g of phenobarbital with their feed in group1 and 4g of phenobarbital per kg of diet in group 2 from day 12 to 18 of the pregnancy (vaginal plug = 1 day). Control female rats were introduced equivalent amount of feed without phenobarbital. The offsprings from both control and treated groups were collected on day 21and at the age of 12 weeks sacrificed with Co2. The body weight of each rat was determined at 3 and 12.The Biceps brachii, Triceps brachii, Soleus,Tibialis, Gastronemius muscle were dissected and were examined, weighed and further fixed in formalin for histomorphological examination. The brains were dissected out, on gross examination, they did not show any difference in morphology between control and treated groups. Histological observation of the treated brains showed dilatation of blood vessels and spongiform changes with scattered patches of gliosis around degenerated cellular mass. Phenobarbital caused widespread apoptotic neurodegeneration in the brains of rats. Subventicular zone was found to be thickened in comparison to the control brains.There was zenkers necrosis and vacuoles in the muscle fibers. There were significant differences between the absolute weights and muscle mass indices of control and prenatally Phenobarbital-exposed groups. Serum Testestron and estrogen was measured by a ELISA technique.There was marked reduction in serum Testestron level in rats in treatment groups. From the result obtained in this study its concluded that phenobarbital damaged the brain cells and subsequently affected the androgen level and muscle in rats prenatally fed with Phenobarbital.
Keywords: Antiepileptic; Apoptosis; Brain; Rat